Socio-cultural factors influencing consent for research in Nigeria: lessons from Pfizer’s trovan clinical trial (2008)
This paper discusses the controversial Trovan study conducted by Pfizer in 1996 in Kano, Nigeria, the peculiar socio-cultural factors that researchers should consider as well as the relevance of the 2007 National Code for Health Research Ethics in enforcing researchers' compliance with ethical standards in informed consent process. Researchers are expected to be sensitive to the many sources of exploitable vulnerability in those whose participation they invite. The failure to give attention to peculiar socio-cultural factors influencing the process of informed consent in Nigeria might have contributed to the failure of many investigators to apply and conform to related local and international research regulations Genuine respect for human dignity requires deeper understanding of patients' values, culture, family and community. Nigeria is socio-culturally diverse in terms of language, religion, economy, and traditions. Investigators require adequate familiarity with the local socio-cultural characteristics in order to meaningfully communicate the research purpose and method upon which free and informed consent is based. The centrality of informed consent in socio-behavioural and health related researches cannot be over emphasized. Negotiating informed consent with the designated authorities in human research with non-Western populations requires investigators to move beyond narrow definitions of personhood, autonomy, and "self" determination. Without these, researchers' efforts would be mere exploitation and abuse of fellow human beings.